Development of new high oleic Sunflower (Helianthus annus L.) hybrids and its genotype × environment interaction across temperature regimes: Development of new high oleic Sunflower (Helianthus annus L.) hybrids and its genotype × environment interaction across temperature regimes - M S UMAR FAROOQ; M S UMA; S D NEHRU (Journal of Oilseeds Research, 2023)
The present investigation was undertaken to assess the stability of 30 sunflower hybrids for oleic acid content along with four commercial checks across three temperature regimes of Karnataka, India over two seasons, rabi/summer 2020-21 and rabi 2021. The phenotypic stability of sunflower hybrids was analyzed by AMMI model. The AMMI biplots delineated one promising hybrid combination which exhibited stable expression of high oleicacid content, with pooled mean of all six environments revealing 73.06 per cent of oleic content. The identification of this particular hybrid combination served the purpose of this study of deriving the stable high oleic hybrid across temperature regimes.